Effectiveness of Cooperative Problem Solving (CPS) Learning with the Science Process Skills Approach on the subject of Simple Harmonic Motion - Rizaldi, Rachmat; Hasanah.S, Uswatun; Syahwin; Fitriana, Sheila; Mardiana, Tri Astuti (Cahaya Ilmu Cendekia Publisher, 2024)
Curpose of the study: The purpose of the research that has been carried out is to analyze the effectiveness of cooperative problem solving learning with the science process skills approach in improving students' understanding of the subject of simple harmonic motion. Methodology: The method used is a quasi-experiment with a pretest-posttest control group design. The subject of the study was students of class X science from two high schools who were selected purposively. The data was analyzed with a Statistical Descriptive Test to describe the learning outcome data from two sample classes. Main Findings: The results of the analysis showed that the average posttest score of the experimental class was higher than that of the control class. The average score of the experimental class showed a high improvement category, while the control class only achieved a moderate category. CPS learning with the SPS approach has proven to be effective because it combines group cooperation and scientific exploration. Students can associate theory with practice, so that the understanding of concepts becomes more deep. Novelty/Originality of this study: This study introduces a novel integration of Cooperative Problem Solving (CPS) with Science Process Skills (SPS) in teaching Simple Harmonic Motion. Unlike traditional methods, this approach fosters both collaborative problem-solving and scientific thinking, enhancing students' conceptual understanding and practical application. It advances existing knowledge by demonstrating how CPS-SPS synergy can bridge theoretical physics and real-world problem-solving skills effectively.